EXCEPTIONS TO THE CRIMINAL JURISDICTION OF THE COASTAL STATE ON MERCHANT AND ON NAVAL VESSELS IN THE HELLENIC LEGAL ORDER - Tryfon, Korontzis (European Scientific Journal, ESJ, 2014)
Hellas as is known possesses one of the most strategic position in the Mediterranean Sea while is between Asia and Europe, near to Africa, between Black sea and Mediterranean Sea, between Eastern and Western Mediterranean. Due its position is rendered nodal point in political, geographic and economic level between the above continents. Hellenic people from the antiquity have developed an intense shipping activity which led them progressively to the configuration of one of the most important shipping forces in world level. Hellas possesses the first position in the European Union (EU) regarding the capacity in tons by vessels under Hellenic flag. Also is between sovereign forces in international level concerning the capacity of vessels under Hellenic flag but also in vessels which are under different flag but are owned by Hellenic ship owners. All these, have led to the configuration and to growth of a law concrete sector, the maritime law, which is constituted by national provisions as also by international provisions.